2022
DOI: 10.3390/eng3020018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Grid Disturbances Caused by Massive Integration of Utility Level Solar Power Systems

Abstract: Solar generation has increased rapidly worldwide in recent years and it is projected to continue to grow exponentially. A problem exists in that the increase in solar energy generation will increase the probability of grid disturbances. This study focuses on analyzing the grid disturbances caused by the massive integration to the transmission line of utility-scale solar energy loaded to the balancing authority high-voltage transmission lines in four regions of the United States electrical system: (1) Californi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Although BEVs and PHEVs do not release emissions, many use grid-connected charging stations that generate a significant percentage of their energy from fossil fuels, which results in critical demand surges in the electrical system [28]. This research builds upon previous studies conducted by the authors [29], extending the examination to the incorporation of solar power facilities within the US at the Balancing Authority level, and its effectiveness in diminishing emissions from fossil fuels. It specifically focuses on the main goal of reducing emissions from fossil fuels.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although BEVs and PHEVs do not release emissions, many use grid-connected charging stations that generate a significant percentage of their energy from fossil fuels, which results in critical demand surges in the electrical system [28]. This research builds upon previous studies conducted by the authors [29], extending the examination to the incorporation of solar power facilities within the US at the Balancing Authority level, and its effectiveness in diminishing emissions from fossil fuels. It specifically focuses on the main goal of reducing emissions from fossil fuels.…”
Section: Introductionmentioning
confidence: 91%
“…The guiding research question is as follows: How does the massive integration of solar power plants impact fossil fuel emission reductions in the US electrical system? By leveraging foundational work in grid disturbances and renewable energy integration [29], this study aims to provide new insights into the scalability and efficiency of solar power systems in reducing fossil fuel dependence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermittent nature of non-dispatchable generation results in unpredictable voltage, current, and frequency profile deviations causing power fluctuations and imbalances in the grid [38]. Distributed energy sources could inject or draw large leading or lagging reactive power and affect the offset load current, voltage drop, and power quality of the grid, thereby increasing harmonics, DC injections and flickers [39]. Furthermore, distributed energy sources can have a variety of effects on the short-circuit current leading to improper protective device coordination and unintended islanding in microgrids, causing equipment damage and delay in service restoration [40].…”
Section: Need Of Sensors In Transmission and Distribution Systemsmentioning
confidence: 99%
“…In the case of residential zones, Fachrizal et al [81] showed that PV and EV exhibit a positive correlation for hosting capacity. Finally, Esteban et al [82] discussed grid disturbances associated with solar energy generation. They showed California's and Southwest's USA net (hourly) energy generation and demand and the energy imbalance taking place in these states with the largest solar energy production.…”
Section: Grid Connectivity and Managementmentioning
confidence: 99%